Venoarterial extracorporeal membrane oxygenation use in staged combined heart–kidney transplant. Issue 1 (20th January 2020) - Al Saadi, Tareq; Sciamanna, Christopher; Andrade, Ambar; Pauwaa, Sunil; Macaluso, Gregory; Joshi, Anjali; Dia, Muhyaldeen; Cotts, William; Pappas, Patroklos; Bresticker, Michael; Tatooles, Antone
Abstract: Outside of heart and lung transplantation, only few cases have been reported describing venoarterial extracorporeal membrane oxygenation (VA-ECMO) use in solid organ transplantation. We present a case of a staged combined heart–kidney transplant in which VA-ECMO was utilized after a complicated orthotopic heart transplantation to successfully complete the subsequent renal transplantation.